Prevalence of obesity, hypertension, and diabetes, and cascade of care in sub-Saharan Africa: a cross-sectional, population-based study in rural and urban Malawi. Issue 3 (March 2018) - Price, Alison J; Crampin, Amelia C; Amberbir, Alemayehu; Kayuni-Chihana, Ndoliwe; Musicha, Crispin; Tafatatha, Terence; Branson, Keith; Lawlor, Debbie A; Mwaiyeghele, Elenaus; Nkhwazi, Lawrence; Smeeth, Liam; Pearce, Neil; et al.
Summary: Background: Sub-Saharan Africa is in rapid demographic transition, and non-communicable diseases are increasingly important causes of morbidity and mortality. We investigated the burden of diabetes, overweight and obesity, hypertension, and multimorbidity, their treatment, and their associations with lifestyle and other factors in Malawi, a very poor country with a predominantly rural—but rapidly growing urban—population, to identify high-risk populations and inform appropriate interventions. Methods: In this cross-sectional, population-based study, we enrolled all adults (≥18 years) residing in two defined geographical areas within Karonga District and Lilongwe city. All adults self-defining as usually resident in the study areas were eligible, and recruited at household level. Participants were interviewed, had anthropometry and blood pressure measured, and had fasting blood samples collected. The study outcomes were prevalence estimates and risk ratios for diabetes (defined as fasting blood glucose of at least 7·0 mmol/L or self-report of a previous diagnosis of diabetes), hypertension (systolic blood pressure of at least 140 mm Hg, diastolic blood pressure of at least 90 mm Hg, or self-report of current antihypertensive medication), overweight (BMI of 25·0–29·9 kg/m 2 ) and obesity (BMI of 30·0 kg/m 2 or more), and multimorbidity (two or more of the above conditions) by location-specific (urban vs rural), age-specific, and sex-specific groups, calculated using negative binomial regression. We used χ 2 likelihood ratio tests to assess heterogeneity by age, location, and sex. Findings: Between May 16, 2013, and Feb 8, 2016, we enrolled 15 013 (62%) of 24 367 eligible urban adults in Lilongwe and 13 878 (88%) of 15 806 eligible rural adults in Karonga District. Overweight and obesity, hypertension, and diabetes were highly prevalent, more so in urban residents, the less poor, and better educated than in rural, the poorest, and least educated participants. 18% of urban men (961 of 5211 participants) and 44% (4115 of 9282) of urban women, and 9% (521 of 5834) of rural men and 27% (2038 of 7497) of rural women were overweight or obese; 16% (859 of 5212), 14% (1349 of 9793), 13% (787 of 5847), and 14% (1101 of 8025) had hypertension; and 3% (133 of 3928), 3% (225 of 7867), 2% (84 of 5004), and 2% (124 of 7116) had diabetes, respectively. Of 566 participants with diabetes, 233 (41%) were undiagnosed, and of 4096 participants with hypertension, 2388 (58%) were undiagnosed. Fewer than half the participants on medication for diabetes or hypertension had well controlled diabetes (84 [41%] of 207 participants) or blood pressure (440 [37%] of 1183 participants). Multimorbidity was highest in urban women (n=519, 7%). Interpretation: Overweight and obesity, hypertension, and diabetes are highly prevalent in urban and rural Malawi, yet many patients are undiagnosed and management is limited. Local-evidence-informed multisectoral, innovative, and targeted interventions are needed urgently to manage the already high burden. Funding: Wellcome Trust.